Legal Certainty of the Existence of Foreign Workers According to Law Number 11 of 2020 Concerning Job Creation - Tine Yowargana; Ramlani Lina Sinaulan; Hedwig Adianto Mau (Jurnal Indonesia Sosial Sains, 2024)
Through Law Number 11 of 2020 on Job Creation, it is easy for foreign workers to enter Indonesia because written permits are replaced by only using a plan for the use of foreign workers. The method used in this research is the normative or legal research method. As a normative legal research, the approach used by the author in discussing this problem is to use a statutory approach. From the results of the research, it is obtained that the policy regarding the regulation of foreign workers in Indonesia has been contained in several regulations, including Minister of Manpower Regulation Number 8 of 2021 which explains the implementation of Government Regulation Number 34 of 2021 concerning the Use of Foreign Workers, as well as Law Number 6 of 2023 which stipulates Government Regulation in Lieu of Law Number 2 of 2022 into the Job Creation Law. The use of foreign workers actually aims to meet the needs of labour with certain skills and expertise in supporting the country's development, especially when the Indonesian workforce is still inadequate in achieving the necessary professionalism. The ratification of Law Number 11 of 2020 brought significant changes in the Labour Law by facilitating the entry of foreign workers into Indonesia, through the deletion and amendment of several articles. In relation to legal certainty regarding the use of foreign workers in Indonesia, Law No. 11/2020 stipulates procedures for the use of foreign workers in Indonesia